2021
DOI: 10.3390/healthcare9030262
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Why All Types of Motivation Are Necessary in Advanced Anaesthesiology Training Levels and How They Influence Job Satisfaction: Translation of the Self-Determination Theory to Healthcare

Abstract: Studies applying the self-determination theory have shown that intrinsic motivation and autonomous regulation lead to job satisfaction and to better job performance. What has not been worked out clearly yet are the effects of extrinsic motivation and controlled regulation on affect, job performance and job satisfaction. However, it has been described that controlled regulation is often necessary for mundane tasks. In anaesthesiology, routine daily tasks can be perceived as mundane by those who have achieved a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
(66 reference statements)
4
2
1
Order By: Relevance
“…On one hand, we found that job resources and demands promoted job satisfaction through strengthening the sense of career calling (H 4a and H 4b ). In other words, more job resources and more moderate job demands predict a higher level of career calling, and therefore predict a higher level of job satisfaction, which was in line with the findings of other studies ( Duffy and Sedlacek, 2007 ; Peng et al, 2019 ; Moll-Khosrawi et al, 2021 ). Moll-Khosrawi et al (2021) studied the relationship between intrinsic motivation and job satisfaction using the self-determination theory.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On one hand, we found that job resources and demands promoted job satisfaction through strengthening the sense of career calling (H 4a and H 4b ). In other words, more job resources and more moderate job demands predict a higher level of career calling, and therefore predict a higher level of job satisfaction, which was in line with the findings of other studies ( Duffy and Sedlacek, 2007 ; Peng et al, 2019 ; Moll-Khosrawi et al, 2021 ). Moll-Khosrawi et al (2021) studied the relationship between intrinsic motivation and job satisfaction using the self-determination theory.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, more job resources and more moderate job demands predict a higher level of career calling, and therefore predict a higher level of job satisfaction, which was in line with the findings of other studies ( Duffy and Sedlacek, 2007 ; Peng et al, 2019 ; Moll-Khosrawi et al, 2021 ). Moll-Khosrawi et al (2021) studied the relationship between intrinsic motivation and job satisfaction using the self-determination theory. They argued that intrinsic motivation and autonomous regulation had effects on job satisfaction, which was positively correlated with intrinsic motivation and negatively correlated with amotivation, mirroring the conclusions of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Managers are advised to identify the needs of nurses and design a relevant motivational program to encourage nurses to achieve maximum performance [55]. Similar to our results, Moll-Khosrawi et al, in 2021, also found that job satisfaction was positively correlated with intrinsic motivation and negatively correlated with amotivation [57].…”
Section: Discussionsupporting
confidence: 89%
“…A unique finding was highlighted by Kearney et al (2023) suggesting that the physical work environment significantly influences job satisfaction, which differs from previous research (Jing et al, 2021;Pandey et al, 2019). Moll-Khosrawi et al (2021) reported that various types of motivation, including autonomous regulation, intrinsic motivation, and amotivation, have correlations with job satisfaction among anesthesiologists. The study suggested that different motivations can coexist within individuals, affecting job satisfaction.…”
Section: Literature Reviewcontrasting
confidence: 59%